The Role and Purpose of Miasms - van der Zee, Harry (Journal of Scientific Exploration, 2025)
The concept of miasms, as introduced and expanded in homeopathic theory, encompasses both individual and collective dimensions of disease and healing. Originating with Samuel Hahnemann’s foundational work, miasms were initially framed as inherited obstacles to health, expressed as chronic diseases and caused by the suppression of infectious diseases. Over time, this understanding has evolved, integrating perspectives on their role in the human evolutionary journey and the individuation process. This paper explores miasms’ function as a catalyst for growth and development. Drawing on theories from homeopathy, epigenetics, and psychology, the work highlights the transformative potential of miasms in fostering awareness and evolution at individual and societal levels. The interplay between suppression, nurturing, and trauma is examined to uncover the broader implications of miasms in health, development, and adaptation. This expanded understanding positions miasms as essential to the dynamism of life and as integral elements of the collective human experience.